Implementation of Interactive Digital Learning Media Using H5P to Improve Learning Material Comprehension of Grade 2 Students at MI Nurud Dzolam Alassumur Kraksaan - Ainur Rofiq Sofa; Moch. Najib Hasbullah Muchlis (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
The integration of interactive digital learning media is increasingly essential to support meaningful learning at the elementary education level. This study aims to examine the implementation of H5P-based interactive digital learning media in improving students’ comprehension of learning materials in Grade II at MI Nurud Dzolam Alassumur Kraksaan. This research employed a qualitative descriptive approach to provide an in-depth understanding of the learning process, teacher practices, and students’ comprehension experiences within a natural classroom setting. Data were collected through classroom observations, in-depth interviews, and documentation, involving the school principal, the vice principal for curriculum affairs, the Islamic Education (PAI) teacher, and Grade II students. The collected data were analyzed using thematic analysis, and the findings were interpreted using Dual Coding theory to explain how the integration of visual, verbal, and interactive elements through H5P supports students’ cognitive processing and learning comprehension. The findings indicate that the implementation of H5P-based interactive learning media was carried out in a structured and engaging manner. H5P features such as interactive videos, quizzes, and drag-and-drop activities enabled students to actively interact with learning content, maintain focus, and understand learning materials more easily. Although challenges related to content preparation, technological limitations, and classroom management were identified, these did not reduce the overall effectiveness of H5P implementation. This study concludes that H5P-based interactive digital learning media effectively enhance students’ comprehension of learning materials and support meaningful learning at the Madrasah Ibtidaiyah level, particularly for lower-grade students.